PENGARUH PAPARAN KADMIUM (Cd) TERHADAP ESTIMASI LAJU FILTRASI GLOMERULUS (eLFG) PADA PEROKOK AKTIF PEKERJA PARKIR DI KELAPA GADING - Mastuti Widi Lestari (Universitas Widya Gama Mahakam Samarinda, 2023)
Background: Conventional smoking activity involve tobacco which will produce smoke which contain toxic substances for the body, especially cadmium (Cd). Cd will enter respiratory tract in form of Cadmium Oxide (CdO) then to lungs and bind to erythrocytes, follow the blood circulation to reach the tissues and organs of the body. In the kidney, a process of reabsorption by proximal tubule will occur and Cd will accumulate, causing interference kidney function. Objectives: Determine whether there was an effect of Cd exposure on eGFR in active smokers among parking attendants in Kelapa Gading Research Metodes: This study used a cross sectional method. The sample used in this study was blood samples from 20 respondents by purposive sampling which were analyzed for Cd levels (ICP-MS) and eGFR (CKD-EPI). Results: The results showed that all respondents had Cd levels in the normal category (< 4.9 µg/L). 80% of respondents had normal eGFR values (≥ 90 ml/minute/1.73 m2) and 20% of them were in the abnormal category (60 - 89 ml/minute/1.73 m2). The result of Pearson's correlation test showed that R = -0.345 <0.468 there is no correlation and confirmed by sample linier regression test result p = 0.136 > 0.05 is meaning no effect. Conclusion: This study is that there was no effect of Cd exposure on eGFR in active smokers among parking attendants in Kelapa Gading